A Ricardian Analysis Of The Impact Of Climate Change On African Cropland - Kurukulasuriya, Pradeep; Mendelsohn, Robert (2007)
This study examines the impact of climate change on cropland in Africa. It is based on a survey of more than 9,000 farmers in 11 countries: Burkina Faso, Cameroon, Egypt, Ethiopia, Ghana, Kenya, Niger, Senegal, South Africa, Zambia, and Zimbabwe. The study uses a Ricardian cross-sectional approach in which net revenue is regressed on climate, water flow, soil, and economic variables. The results show that net revenues fall as precipitation falls or as temperatures warm across all the surveyed farms. In addition to examining all farms together, the study examined dryland and irrigated farms separately. Dryland farms are especially climate sensitive. Irrigated farms have a positive immediate response to warming because they are located in relatively cool parts of Africa. The study also examined some simple climate scenarios to see how Africa would respond to climate change. These uniform scenarios assume that only one aspect of climate changes and the change is uniform across all of Africa. In addition, the study examined three climate change scenarios from Atmospheric Oceanic General Circulation Models. These scenarios predicted changes in climate in each country over time. Not all countries are equally vulnerable to climate change. First, the climate scenarios predict different temperature and precipitation changes in each country. Second, it is also important whether a country is already hot and dry. Third, the extent to which farms are irrigated is also important.
openalex: W3123418393 mag: 3123418393
Keywords: openalex:import

A Ricardian Analysis Of The Impact Of Climate Change On African Cropland - Kurukulasuriya, Pradeep; Mendelsohn, Robert (2007)
This study examines the impact of climate change on cropland in Africa. It is based on a survey of more than 9,000 farmers in 11 countries: Burkina Faso, Cameroon, Egypt, Ethiopia, Ghana, Kenya, Niger, Senegal, South Africa, Zambia, and Zimbabwe. The study uses a Ricardian cross-sectional approach in which net revenue is regressed on climate, water flow, soil, and economic variables. The results show that net revenues fall as precipitation falls or as temperatures warm across all the surveyed farms. In addition to examining all farms together, the study examined dryland and irrigated farms separately. Dryland farms are especially climate sensitive. Irrigated farms have a positive immediate response to warming because they are located in relatively cool parts of Africa. The study also examined some simple climate scenarios to see how Africa would respond to climate change. These uniform scenarios assume that only one aspect of climate changes and the change is uniform across all of Africa. In addition, the study examined three climate change scenarios from Atmospheric Oceanic General Circulation Models. These scenarios predicted changes in climate in each country over time. Not all countries are equally vulnerable to climate change. First, the climate scenarios predict different temperature and precipitation changes in each country. Second, it is also important whether a country is already hot and dry. Third, the extent to which farms are irrigated is also important.
openalex: W3123418393 mag: 3123418393
Keywords: openalex:import

A Ricardian Analysis Of The Impact Of Climate Change On African Cropland - Kurukulasuriya, Pradeep; Mendelsohn, Robert (2007)
This study examines the impact of climate change on cropland in Africa. It is based on a survey of more than 9,000 farmers in 11 countries: Burkina Faso, Cameroon, Egypt, Ethiopia, Ghana, Kenya, Niger, Senegal, South Africa, Zambia, and Zimbabwe. The study uses a Ricardian cross-sectional approach in which net revenue is regressed on climate, water flow, soil, and economic variables. The results show that net revenues fall as precipitation falls or as temperatures warm across all the surveyed farms. In addition to examining all farms together, the study examined dryland and irrigated farms separately. Dryland farms are especially climate sensitive. Irrigated farms have a positive immediate response to warming because they are located in relatively cool parts of Africa. The study also examined some simple climate scenarios to see how Africa would respond to climate change. These uniform scenarios assume that only one aspect of climate changes and the change is uniform across all of Africa. In addition, the study examined three climate change scenarios from Atmospheric Oceanic General Circulation Models. These scenarios predicted changes in climate in each country over time. Not all countries are equally vulnerable to climate change. First, the climate scenarios predict different temperature and precipitation changes in each country. Second, it is also important whether a country is already hot and dry. Third, the extent to which farms are irrigated is also important.
openalex: W3123418393 mag: 3123418393
Keywords: openalex:import

A Ricardian Analysis Of The Impact Of Climate Change On African Cropland - Kurukulasuriya, Pradeep; Mendelsohn, Robert (2007)
This study examines the impact of climate change on cropland in Africa. It is based on a survey of more than 9,000 farmers in 11 countries: Burkina Faso, Cameroon, Egypt, Ethiopia, Ghana, Kenya, Niger, Senegal, South Africa, Zambia, and Zimbabwe. The study uses a Ricardian cross-sectional approach in which net revenue is regressed on climate, water flow, soil, and economic variables. The results show that net revenues fall as precipitation falls or as temperatures warm across all the surveyed farms. In addition to examining all farms together, the study examined dryland and irrigated farms separately. Dryland farms are especially climate sensitive. Irrigated farms have a positive immediate response to warming because they are located in relatively cool parts of Africa. The study also examined some simple climate scenarios to see how Africa would respond to climate change. These uniform scenarios assume that only one aspect of climate changes and the change is uniform across all of Africa. In addition, the study examined three climate change scenarios from Atmospheric Oceanic General Circulation Models. These scenarios predicted changes in climate in each country over time. Not all countries are equally vulnerable to climate change. First, the climate scenarios predict different temperature and precipitation changes in each country. Second, it is also important whether a country is already hot and dry. Third, the extent to which farms are irrigated is also important.
openalex: W3123418393 mag: 3123418393
Keywords: openalex:import

Endogenous irrigation : the impact of climate change on farmers in Africa - Mendelsohn, Robert; Kurukulasuriya, Pradeep (2007)
Previous Ricardian analyses of agriculture have either omitted irrigation or treated irrigation as though it is exogenous. In practice, it is a choice by farmers that is sensitive to climate. This paper develops a choice model of irrigation in the context of a Ricardian model of cropland. The authors examine how climate affects the decision to use irrigation and then how climate affects the net revenues of dryland and irrigated land. This Ricardian 'selection' model, using a modified Heckman model, is then estimated across 8,400 farmers in Africa. The analysis explicitly models irrigation but controls for the endogeneity of irrigation. The authors find that the choice of irrigation is sensitive to both temperature and precipitation. Simulations of the welfare impacts of several climate scenarios demonstrate that a model which assumes irrigation is exogenous provides a biased estimate of the welfare effects of climate change. If dryland and irrigation are to be estimated separately in the Ricardian model, irrigation must be modeled endogenously. The results also indicate that African agriculture is sensitive to climate change. Many farmers in Africa will experience net revenue losses from warming. Irrigated farms, on the other hand, are more resilient to temperature change and, on the margin, are likely to realize slight gains in productivity. But any reduction in precipitation will be especially deleterious to dryland farmers, generally the poorest segment of the agriculture community. The results indicate that irrigation is an effective adaptation against loss of rainfall and higher temperatures provided there is sufficient water available. This will be an effective remedy in select regions of Africa with water. However, for many regions there is no available surface water, so that warming scenarios with reduced rainfall are particularly deleterious.
openalex: W2099443078 mag: 2099443078
Keywords: openalex:import

A Ricardian Analysis of the Impact of Climate Change on African Cropland - Kurukulasuriya, Pradeep; Mendelsohn, Robert (Social Science Research Network, 2007)
This study examines the impact of climate change on cropland in Africa. It is based on a survey of more than 9,000 farmers in 11 countries: Burkina Faso, Cameroon, Egypt, Ethiopia, Ghana, Kenya, Niger, Senegal, South Africa, Zambia, and Zimbabwe. The study uses a Ricardian cross-sectional approach in which net revenue is regressed on climate, water flow, soil, and economic variables. The results show that net revenues fall as precipitation falls or as temperatures warm across all the surveyed farms. In addition to examining all farms together, the study examined dryland and irrigated farms separately. Dryland farms are especially climate sensitive. Irrigated farms have a positive immediate response to warming because they are located in relatively cool parts of Africa. The study also examined some simple climate scenarios to see how Africa would respond to climate change. These uniform scenarios assume that only one aspect of climate changes and the change is uniform across all of Africa. In addition, the study examined three climate change scenarios from Atmospheric Oceanic General Circulation Models. These scenarios predicted changes in climate in each country over time. Not all countries are equally vulnerable to climate change. First, the climate scenarios predict different temperature and precipitation changes in each country. Second, it is also important whether a country is already hot and dry. Third, the extent to which farms are irrigated is also important.
openalex: W1730679139 mag: 1730679139
Keywords: openalex:import

How Will Climate Change Shift Agro-Ecological Zones And Impact African Agriculture? - Kurukulasuriya, Pradeep; Mendelsohn, Robert (2008)
The study develops a new method to measure the impacts of climate change on agriculture called the Agro-Ecological Zone (AEZ) Model. A multinomial logit is estimated to predict the probability of each AEZ in each district. The average percentage of cropland and average crop net revenue are calculated for each AEZ. Then an estimate of the amount of cropland in Africa and where it is located is provided. Using current conditions, the model calculates baseline values of cropland and crop net revenue, and estimates the future impact of climate change using two scenarios-harsh and mild. Total cropland does not change much across the two climate scenarios. However, the predicted change in African crop revenue ranges from a loss of 14 percent in the mild climate scenario to 30 percent in the harsher climate scenario. The analysis reveals that the greatest harm from climate change is that it will shift farms from high to low productive AEZs. The approach not only identifies the aggregate impacts, but also indicates where the impacts occur across Africa. The central region of Africa is hurt the most, especially in the harsher climate scenario. The Agro-Ecological Zone Model is a promising new method for valuing the long-term impacts of climate change on agriculture.
openalex: W1514110752 mag: 1514110752
Keywords: openalex:import

A ricardian analysis of the impact of climate change on African cropland - Kurukulasuriya, Pradeep; Mendelsohn, Robert (RePEc: Research Papers in Economics, 2007)
This study examines the impact of climate change on cropland in Africa. It is based on a survey of more than 9,000 farmers in 11 countries: Burkina Faso, Cameroon, Egypt, Ethiopia, Ghana, Kenya, Niger, Senegal, South Africa, Zambia, and Zimbabwe. The study uses a Ricardian cross-sectional approach in which net revenue is regressed on climate, water flow, soil, and economic variables. The results show that net revenues fall as precipitation falls or as temperatures warm across all the surveyed farms. In addition to examining all farms together, the study examined dryland and irrigated farms separately. Dryland farms areespecially climate sensitive. Irrigated farms have a positive immediate response to warming because they are located in relatively cool parts of Africa. The study also examined some simple climate scenarios to see how Africa would respond to climate change. These uniform scenarios assume that only one aspect of climate changes and the change is uniform across all of Africa. In addition, the study examined three climate change scenarios from Atmospheric Oceanic General Circulation Models. These scenarios predicted changes in climate in each country over time. Not all countries are equally vulnerable to climate change. First, the climate scenarios predict different temperature and precipitation changes in each country. Second, it is also important whether a country is already hot and dry. Third, the extent to which farms are irrigated is also important.
openalex: W3121337576 mag: 3121337576
Keywords: openalex:import

How will climate change shift agro-ecological zones and impact African agriculture ? - Kurukulasuriya, Pradeep; Mendelsohn, Robert (RePEc: Research Papers in Economics, 2008)
The study develops a new method to measure the impacts of climate change on agriculture called the Agro-Ecological Zone (AEZ) Model. A multinomial logit is estimated to predict the probability of each AEZ in each district. The average percentage of cropland and average crop net revenue are calculated for each AEZ. Then an estimate of the amount of cropland in Africa and where it is located is provided. Using current conditions, the model calculates baseline values of cropland and crop net revenue, and estimates the future impact of climate change using two scenarios-harsh and mild. Total cropland does not change much across the two climate scenarios. However, the predicted change in African crop revenue ranges from a loss of 14 percent in the mild climate scenario to 30 percent in the harsher climate scenario. The analysis reveals that the greatest harm from climate change is that it will shift farms from high to low productive AEZs. The approach not only identifies the aggregate impacts, but also indicates where the impacts occur across Africa. The central region of Africa is hurt the most, especially in the harsher climate scenario. The Agro-Ecological Zone Model is a promising new method for valuing the long-term impacts of climate change on agriculture.
openalex: W3121355165 mag: 3121355165
Keywords: openalex:import

Endogenous irrigation : the impact of climate change on farmers in Africa - Kurukulasuriya, Pradeep; Mendelsohn, Robert (RePEc: Research Papers in Economics, 2007)
Previous Ricardian analyses of agriculture have either omitted irrigation or treated irrigation as though it is exogenous. In practice, it is a choice by farmers that is sensitive to climate. This paper develops a choice model of irrigation in the context of a Ricardian model of cropland. The authors examine how climate affects the decision to use irrigation and then how climate affects the net revenues of dryland and irrigated land. This Ricardianselectionmodel, using a modified Heckman model, is then estimated across 8,400 farmers in Africa. The analysis explicitly models irrigation but controls for the endogeneity of irrigation. The authors find that the choice of irrigation is sensitive to both temperature and precipitation. Simulations of the welfare impacts of several climate scenarios demonstrate that a model which assumes irrigation is exogenous provides a biased estimate of the welfare effects of climate change. If dryland and irrigation are to be estimated separately in the Ricardian model, irrigation must be modeled endogenously. The results also indicate that African agriculture is sensitive to climate change. Many farmers in Africa will experience net revenue losses from warming. Irrigated farms, on the other hand, are more resilient to temperature change and, on the margin, are likely to realize slight gains in productivity. But any reduction in precipitation will be especially deleterious to dryland farmers, generally the poorest segment of the agriculture community. The results indicate that irrigation is an effective adaptation against loss of rainfall and higher temperatures provided there is sufficient water available. This will be an effective remedy in select regions of Africa with water. However, for many regions there is no available surface water, so that warming scenarios with reduced rainfall are particularly deleterious.
openalex: W3124585754 mag: 3124585754
Keywords: openalex:import

Climate change adaptation in Africa : a microeconomic analysis of livestock choice - Seo, S. Niggol; Mendelsohn, Robert (2007)
This paper uses quantitative methods to examine the way African farmers have adapted livestock management to the range of climates found across the African continent. The authors use logit analysis to estimate whether farmers adopt livestock. They then use three econometric models to examine which species farmers choose: a primary choice multinomial logit, an optimal portfolio multinomial logit, and a demand system multivariate probit. Comparing the results of the three methods of estimating species selection reveals that the three approaches yield similar results. Using data from over 9,000 African livestock farmers in 10 countries, the analysis finds that farmers are more likely to choose to have livestock as temperatures increase and as precipitation decreases. Across all methods of estimating choice, livestock farmers in warmer locations are less likely to choose beef cattle and chickens and more likely to choose goats and sheep. As precipitation increases, cattle and sheep decrease but goats and chickens increase. The authors simulate the way farmers' choices might change with a set of uniform climate changes and a set of climate model scenarios. The uniform scenarios predict that warming and drying would increase livestock ownership but that increases in precipitation would decrease it. The climate scenarios predict a decrease in the probability of beef cattle and an increase in the probability of sheep and goats, and they predict that more heat-tolerant animals will dominate the future African landscape.
openalex: W1549666903 mag: 1549666903
Keywords: openalex:import

Measuring impacts and adaptations to climate change: a structural Ricardian model of African livestock management^1 - Seo, S. Niggol; Mendelsohn, Robert (Agricultural Economics, 2008)
Abstract This article develops a new cross‐sectional methodology that explicitly incorporates adaptation into an analysis of the impacts of climate change. The methodology examines how a farmer will change choices of species and number to adapt to climate. The approach is applied to study Africa, where the impacts of climate change are expected to be the most severe. The results indicate that in warmer places, African farmers switch from beef cattle to more heat‐tolerant goats and sheep. In wetter places, farmers switch from cattle and sheep to goats and chickens. The results indicate that large commercial livestock operations specializing in beef cattle will be hard hit from climate change whereas small farmers who can easily substitute to goats and/or sheep will be more resilient.
openalex: W2154895706 mag: 2154895706
Keywords: openalex:import

Animal husbandry in Africa: Climate change impacts and adaptations - Seo, S. Niggol; Mendelsohn, Robert (African Journal of Agricultural and Resource Economics, 2008)
This paper uses a cross-sectional approach to analyze the impacts of climate change on animal husbandry and the way farmers adapt. The study is based on surveys of almost 5000 livestock farmers across ten countries in Africa. A traditional Ricardian regression finds that the livestock net revenues of large farms in Africa are more sensitive to temperature than those of small farms. Cross-sectional analysis also reveals that large farms (but not small farms) have fewer animals per farm in warmer places. Farmers tend to select beef cattle and chickens in cool climates and goats and sheep in hot climates. Using the Ricardian results and examining climate scenarios for 2060 and beyond, the net revenues of small farms are predicted to increase as much as 120% (+USD6 billion) but those of large farms are predicted to fall by 20% (-USD12 billion). The impact estimates in any given period also depend on the rainfall predictions. The results suggest that large livestock farms in Africa are more sensitive to temperature than small ones, primarily because of their dependence on cattle.
openalex: W2156213154 mag: 2156213154
Keywords: openalex:import

Measuring impacts and adaptations to climate change: a structural Ricardian model of African livestock management - Seo, S. Niggol; Mendelsohn, Robert (Agricultural Economics, 2008)
openalex: W4233307230
Keywords: openalex:import

The impact of climate change on livestock management in Africa : a structural Ricardian analysis - Seo, S. Niggol; Mendelsohn, Robert (2007)
This paper develops the structural Ricardian method, a new approach to modeling agricultural performance using cross-sectional evidence, and uses the method to study animal husbandry in Africa. The model is intended to estimate the structure beneath Ricardian results in order to understand how farmers change their behavior in response to climate. A survey of over 5,000 livestock farmers in 10 countries reveals that the selection of species, the net income per animal, and the number of animals are all highly dependent on climate. As climate warms, net income across all animals will fall, especially across beef cattle. The fall in net income causes African farmers to reduce the number of animals on their farms. The fall in relative revenues also causes them to shift away from beef cattle and toward sheep and goats. All farmers will lose income but the most vulnerable farms are large African farms that currently specialize in beef cattle. Small livestock and large livestock farms respond to climates differently. Small farms are diversified, relying on dairy cattle, goats, sheep, and chickens. Large farms specialize in dairy and beef cattle. Estimating a separate multinomial logit selection model for small and large farms reveals that the two types of farm choose species differently and specifically have different climate response functions. The regressions of the number of animals also reveal that large farms are more responsive to climate. The results indicate that warming will be harmful to commercial livestock owners, especially cattle owners. Owners of commercial livestock farms have few alternatives either in crops or other animal species. In contrast, small livestock farms are better able to adapt to warming or precipitation increases by switching to heat tolerant animals or crops. Livestock operations will be a safety valve for small farmers if warming or drought causes their crops to fail.
openalex: W1939364766 mag: 1939364766
Keywords: openalex:import

Climate change impacts on animal husbandry in Africa: a Ricardian analysis - Mendelsohn, Robert; Seo, S. Niggol (RePEc: Research Papers in Economics, 2007)
This paper analyzes the impact of climate change on animal husbandry in Africa. It regresses the net revenue from raising animals in small and large farms across Africa on climate, soil, and other control variables to test the climate sensitivity of livestock. The study is based on a survey of over 9,000 farmers across 11 countries conducted by the World Bank and the Global Environment Facility. From this dataset, 5,400 farms were found to rely on livestock. The paper develops models to test whether the climate coefficients of small and large farms are similar. It turns out that small farms tend to be more labor intensive, rely on native stocks, and have few animals. Large farms tend to be more commercial operations, with much larger stocks and more modern approaches. The analysis finds that warming is good for small farms because they can substitute animals that are heat tolerant. Large farms, by contrast, are more dependent on cattle, which are not heat tolerant. The wetter scenarios are likely to be harmful to grazing animals because greater rainfall implies a shift from grasslands to forests, an increase in harmful disease vectors, and a shift from livestock to crops. Overall, because large farms dominate the sector, African livestock net revenues are expected to fall. However, if future climates turn out to be dry, livestock net revenue will increase. At least against the risk of dryness, livestock offer a good substitute for crops.
openalex: W3121448396 mag: 3121448396
Keywords: openalex:import

A Structural Ricardian Analysis Of Climate Change Impacts And Adaptations In African Agriculture - Seo, S. Niggol; Mendelsohn, Robert (2008)
This paper develops a Structural Ricardian model to measure climate change impacts that explicitly models the choice of farm type in African agriculture. This two stage model first estimates the type of farm chosen and then the conditional incomes of each farm type after removing selection biases. The results indicate that increases in temperature encourage farmers to adopt mixed farming and avoid specialized farms such as crop-only or livestock-only farms. Increases in precipitation encourage farmers to shift from irrigated to rainfed crops. As temperatures increase, farm incomes from crop-only farms or livestock-only farms fall whereas incomes from mixed farms increase. With precipitation increases, farm incomes from irrigated farms fall whereas incomes from rainfed farms increase. Naturally, the Structural Ricardian model predicts much smaller impacts than a model that holds farm type fixed. With a hot dry climate scenario, the Structural Ricardian model predicts that farm income will fall 50 percent but the fixed farm type model predicts farm incomes will fall 75 percent.
openalex: W1939656838 mag: 1939656838
Keywords: openalex:import

Climate Change Impacts On Animal Husbandry In Africa : A Ricardian Analysis - Seo, S. Niggol; Mendelsohn, Robert (2007)
This paper analyzes the impact of climate change on animal husbandry in Africa. It regresses the net revenue from raising animals in small and large farms across Africa on climate, soil, and other control variables to test the climate sensitivity of livestock. The study is based on a survey of over 9,000 farmers across 11 countries conducted by the World Bank and the Global Environment Facility. From this dataset, 5,400 farms were found to rely on livestock. The paper develops models to test whether the climate coefficients of small and large farms are similar. It turns out that small farms tend to be more labor intensive, rely on native stocks, and have few animals. Large farms tend to be more commercial operations, with much larger stocks and more modern approaches. The analysis finds that warming is good for small farms because they can substitute animals that are heat tolerant. Large farms, by contrast, are more dependent on cattle, which are not heat tolerant. The wetter scenarios are likely to be harmful to grazing animals because greater rainfall implies a shift from grasslands to forests, an increase in harmful disease vectors, and a shift from livestock to crops. Overall, because large farms dominate the sector, African livestock net revenues are expected to fall. However, if future climates turn out to be dry, livestock net revenue will increase. At least against the risk of dryness, livestock offer a good substitute for crops.
openalex: W2157628084 mag: 2157628084
Keywords: openalex:import

The impact of climate change on agricultural net revenue: a case study in the Fouta Djallon, West Africa - Wood, Stephen A.; Mendelsohn, Robert (Environment and Development Economics, 2014)
Abstract Continental-scale economic analysis suggests that changes in climate conditions are associated with lower agricultural net revenue in sub-Saharan Africa. Specific locations, however, may not reflect this overall trend due to variation in baseline climate, soils, and socioeconomic factors that are difficult to model at large scales. The economic effect of changes in climate conditions on agricultural revenue in particular places in sub-Saharan Africa remains largely unknown. To test this effect, we study an area of West Africa with high climate variation over a small geographic area. We find that higher temperatures and precipitation lower agricultural revenues in the more important rainy season but increase revenues in the less important cool, dry season.
openalex: W2135114510 mag: 2135114510
Keywords: openalex:import

The impact of climate change on livestock management in Africa : a structural Ricardian analysis - Seo, S. Niggol; Mendelsohn, Robert (RePEc: Research Papers in Economics, 2007)
This paper develops the structural Ricardian method, a new approach to modeling agricultural performance using cross-sectional evidence, and uses the method to study animal husbandry in Africa. The model is intended to estimate the structure beneath Ricardian results in order to understand how farmers change their behavior in response to climate. A survey of over 5,000 livestock farmers in 10 countries reveals that the selection of species, the net income per animal, and the number of animals are all highly dependent on climate. As climate warms, net income across all animals will fall, especially across beef cattle. The fall in net income causes African farmers to reduce the number of animals on their farms. The fall in relative revenues also causes them to shift away from beef cattle and toward sheep and goats. All farmers will lose income but the most vulnerable farms are large African farms that currently specialize in beef cattle. Small livestock and large livestock farms respond to climates differently. Small farms are diversified, relying on dairy cattle, goats, sheep, and chickens. Large farms specialize in dairy and beef cattle. Estimating a separate multinomial logit selection model for small and large farms reveals that the two types of farm choose species differently and specifically have different climate response functions. The regressions of the number of animals also reveal that large farms are more responsive to climate. The results indicate that warming will be harmful to commercial livestock owners, especially cattle owners. Owners of commercial livestock farms have few alternatives either in crops or other animal species. In contrast, small livestock farms are better able to adapt to warming or precipitation increases by switching to heat tolerant animals or crops. Livestock operations will be a safety valve for small farmers if warming or drought causes their crops to fail.
openalex: W3123417404 mag: 3123417404
Keywords: openalex:import

Climate change adaptation in Africa: a microeconomic analysis of livestock choice - Seo, S. Niggol; Mendelsohn, Robert (RePEc: Research Papers in Economics, 2007)
This paper uses quantitative methods to examine the way African farmers have adapted livestock management to the range of climates found across the African continent. The authors use logit analysis to estimate whether farmers adopt livestock. They then use three econometric models to examine which species farmers choose: a primary choice multinomial logit, an optimal portfolio multinomial logit, and a demand system multivariate probit. Comparing the results of the three methods of estimating species selection reveals that the three approaches yield similar results. Using data from over 9,000 African livestock farmers in 10 countries, the analysis finds that farmers are more likely to choose to have livestock as temperatures increase and as precipitation decreases. Across all methods of estimating choice, livestock farmers in warmer locations are less likely to choose beef cattle and chickens and more likely to choose goats and sheep. As precipitation increases, cattle and sheep decrease but goats and chickens increase. The authors simulate the way farmers'choices might change with a set of uniform climate changes and a set of climate model scenarios. The uniform scenarios predict that warming and drying would increase livestock ownership but that increases in precipitation would decrease it. The climate scenarios predict a decrease in the probability of beef cattle and an increase in the probability of sheep and goats, and they predict that more heat-tolerant animals will dominate the future African landscape.
openalex: W3123833773 mag: 3123833773
Keywords: openalex:import

A structural ricardian analysis of climate change impacts and adaptations in African agriculture - Seo, S. Niggol; Mendelsohn, Robert (RePEc: Research Papers in Economics, 2008)
This paper develops a Structural Ricardian model to measure climate change impacts that explicitly models the choice of farm type in African agriculture. This two stage model first estimates the type of farm chosen and then the conditional incomes of each farm type after removing selection biases. The results indicate that increases in temperature encourage farmers to adopt mixed farming and avoid specialized farms such as crop-only or livestock-only farms. Increases in precipitation encourage farmers to shift from irrigated to rainfed crops. As temperatures increase, farm incomes from crop-only farms or livestock-only farms fall whereas incomes from mixed farms increase. With precipitation increases, farm incomes from irrigated farms fall whereas incomes from rainfed farms increase. Naturally, the Structural Ricardian model predicts much smaller impacts than a model that holds farm type fixed. With a hot dry climate scenario, the Structural Ricardian model predicts that farm income will fall 50 percent but the fixed farm type model predicts farm incomes will fall 75 percent.
openalex: W3124153085 mag: 3124153085
Keywords: openalex:import

ADAPTATION AND CLIMATE CHANGE IMPACTS: A STRUCTURAL RICARDIAN MODEL OF IRRIGATION AND FARM INCOME IN AFRICA - Kurukulasuriya, Pradeep; Kala, Namrata; Mendelsohn, Robert (Climate Change Economics, 2011)
Although there is now an extensive literature on the economic impacts of climate change on agriculture, no study has yet addressed the endogeneity of irrigation. This paper examines how climate affects the choice to irrigate and the conditional income earned by each farmer. The paper develops a selection model of irrigation choice and conditional income. Using data from farmers across eleven African countries, the paper demonstrates that the choice of irrigation is sensitive to both temperature and precipitation. Rainfed and irrigated farm income also both respond to climate but have different climate sensitivity. Impact models that fail to account for endogenous irrigation are biased.
openalex: W2029819114 mag: 2029819114
Keywords: openalex:import

The impact of climate change on agro-ecological zones: evidence from Africa - Kala, Namrata; Kurukulasuriya, Pradeep; Mendelsohn, Robert (Environment and Development Economics, 2012)
Abstract This study predicts the impact of climate change on African agriculture. We use a generalized linear model (GLM) framework to estimate the relationship between the proportion of various Agro-Ecological Zones (AEZs) in a district and climate. Using three climate scenarios, we project how climate change will cause AEZs to shift, causing changes in acreage and net revenue per hectare of cropland. Our results predict that Africa will suffer heavy annual welfare losses by 2070–2100, ranging between US$14 billion and US$70 billion, depending on the climate scenario and cropland measure considered.
openalex: W2040121897 mag: 2040121897
Keywords: openalex:import

Economic vulnerability to tropical storms on the southeastern coast of Africa - Molua, Ernest L.; Mendelsohn, Robert; Akamin, Ajapnwa (Jàmbá, 2020)
Climate change will hit Africa economically hard, not least Southeast Africa. Understanding the impact of extreme climatic events is important for both economic development and climate change policy. Global climatological summaries reveal high damage potential pathways for developed countries. Will countries in Africa, especially in the southeastern board of the continent, be vulnerable to loss-generating extreme climate events? This study examined for countries in the sub-region, their vulnerability and damage costs, the impact of climate change on tropical storm damage, as well as the differential impacts of storm damages. An approach using a combination of physical and economic reasoning, as well as results of previous studies, reveals that in Southeast Africa, the economic response to the key damage parameters of intensity, size and wind speed is significant for all the countries. Damages in Kenya and Tanzania are sensitive to wind speed. Both vulnerability and adaptation are important for Madagascar and Mozambique - two countries predicted to be persistently damaged by tropical storms. For Mauritius and South Africa, inflictions from extreme events are expected to be impactful, and would require resilient public and private infrastructure. Reducing the physical and socio-economic vulnerability to extreme events will require addressing the underlying socio-economic drivers, as well as developing critical public infrastructure.
openalex: W3093175541 mag: 3093175541
Keywords: openalex:import

Climate Change and Agriculture in Africa: Impact Assessment and Adaptation Strategies - Dinar, Ariel; Hassan, Rashid M.; Mendelsohn, Robert; Benhin, James (2008)
Foreword * Introduction and Rationale * Study Objectives, Structure, Methodology, Organization and Countries Agroclimatic Conditions * Methods and Models Developed and Used in the Study * Results of the Country Analyses * Results of the Regional Analyses * Summary, Conclusions and Policy Implications * Index
openalex: W1549909674 mag: 1549909674
Keywords: openalex:import

Adapting to Climate Change Mosaically: An Analysis of African Livestock Management by Agro-Ecological Zones - Seo, S. Niggol; Mendelsohn, Robert; Dinar, Ariel; Kurukulasuriya, Pradeep (B E Journal of Economic Analysis & Policy, 2009)
Abstract This paper examines African livestock management across Agro-Ecological Zones (AEZs) to learn how they would adapt to climate change in the coming century. We analyze farm level decisions to own livestock and to choose a primary livestock species using logit models with and without country fixed effects or AEZ fixed effects. With a hot dry scenario, the results indicate that livestock ownership will increase slightly across all of Africa, but especially in West Africa and high elevation AEZs. Dairy cattle will decrease in semi-arid regions, sheep will increase in lowlands, and rearing chickens will increase at high elevations. On the other hand, if climate becomes wetter, livestock ownership will fall dramatically in lowlands and high elevation moist AEZs. Beef cattle will increase and sheep will fall in dry AEZs, dairy cattle will fall precipitously and goats will rise in moist AEZs, and chickens will increase at high elevations but fall at mid elevations. Therefore, adaptation measures should be tailored to a specific AEZ.
openalex: W2135202551 mag: 2135202551
Keywords: openalex:import

Climate Change and Agriculture in Africa - Dinar, Ariel; Hassan, Rashid M.; Mendelsohn, Robert; Benhin, James; al., et (2012)
openalex: W4246741985
Keywords: openalex:import

A Ricardian Analysis of the Distribution of Climate Change Impacts on Agriculture across Agro-Ecological Zones in Africa - Seo, S. Niggol; Mendelsohn, Robert; Dinar, Ariel; Hassan, Rashid M.; Kurukulasuriya, Pradeep (Environmental and Resource Economics, 2009)
This paper examines the distribution of climate change impacts across the sixteen Agro-Ecological Zones (AEZs) of Africa. We combine net revenue from livestock and crops and regress total net revenue on a set of climate, soil, and socio-economic variables with and without country fixed effects. Although African crop net revenue is very sensitive to climate change, combined livestock and crop net revenue is more climate resilient. With the hot and dry CCC climate scenario, average damage estimates reach 27% by 2100, but with the mild and wet PCM scenario, African farmers will benefit. The analysis of AEZs implies that the effects of climate change will be quite different across Africa. For example, currently productive areas such as dry/moist savannah are more vulnerable to climate change while currently less productive agricultural zones such as humid forest or sub-humid AEZs become more productive in the future.
openalex: W3122897265 mag: 3122897265
Keywords: openalex:import

A Ricardian Analysis Of The Distribution Of Climate Change Impacts On Agriculture Across Agro-Ecological Zones In Africa - Seo, S. Niggol; Mendelsohn, Robert; Dinar, Ariel; Hassan, Rashid M.; Kurukulasuriya, Pradeep (2008)
This paper examines the distribution of climate change impacts across the six- teen Agro-Ecological Zones (AEZs) of Africa. We combine net revenue from livestock and
openalex: W2129008158 mag: 2129008158
Keywords: openalex:import

Differential Adaptation Strategies To Climate Change In African Cropland By Agro-Ecological Zones - Seo, S. Niggol; Mendelsohn, Robert; Kurukulasuriya, Pradeep; Dinar, Ariel; Hassan, Rashid M. (2008)
This paper quantifies how African farmers have adapted their crop and irrigation decisions to their farm's current agro-ecological zone. The results indicate that farmers carefully consider the climate and other conditions of their farm when making these choices. These results are then used to forecast how farmers might change their irrigation and crop choice decisions if climate changes. The model predicts African farmers would adopt irrigation more often under a very hot and dry climate scenario but less often with a mild and wet scenario. However, farms in the deserts, lowland humid forest, or mid elevation humid forest would reduce irrigation even in the very hot and dry climate scenario. Area under fruits and vegetables would increase Africa-wide with the very hot and dry climate scenario, except in the lowland semi-arid agro-ecological zone. Millet would increase overall under the mild and wet scenario, but decline substantially in the lowland dry savannah and lowland semi-arid agro-ecological zones. Maize would be chosen less often across all the agro-ecological zones under both climate scenarios. Wheat would decrease across Africa. The authors recommend that care must be taken to match adaptations to local conditions because the optimal adaptation would depend on the agro-ecological zone and the climate scenario.
openalex: W1921662985 mag: 1921662985
Keywords: openalex:import

A Ricardian Analysis of the Distribution of Climate Change Impacts on Agriculture Across Agro-Ecological Zones in Africa - Seo, S. Niggol; Mendelsohn, Robert; Dinar, Ariel; Hassan, Rashid M.; Kurukulasuriya, Pradeep (Social Science Research Network, 2008)
This paper examines the distribution of climate change impacts across the 16 agro-ecological zones in Africa using data from the Food and Agriculture Organization combined economic survey data from a Global Environment Facility/World Bank project. Net revenue per hectare of cropland is regressed on a set of climate, soil, and socio-economic variables using different econometric specifications with and without country fixed effects. Country fixed effects slightly reduce predicted future climate related damage to agriculture. With a mild climate scenario, African farmers gain income from climate change; a more severe scenario, they lose income. Some locations are more affected than others. The analysis of agro-ecological zones implies that the effects of climate change will vary across Africa. For example, currently productive areas such as dry/moist savannah are more vulnerable to climate change while currently less productive agricultural zones such as humid forest or sub-humid zones become more productive in the future. The agro-ecological zone classification can help explain the variation of impacts across the landscape.
openalex: W3122458275 mag: 3122458275
Keywords: openalex:import

Differential adaptation strategies to climate change in African cropland by agro-ecological zones - Seo, S. Niggol; Mendelsohn, Robert; Kurukulasuriya, Pradeep; Dinar, Ariel; Hassan, Rashid M. (RePEc: Research Papers in Economics, 2008)
This paper quantifies how African farmers have adapted their crop and irrigation decisions to their farm's current agro-ecological zone. The results indicate that farmers carefully consider the climate and other conditions of their farm when making these choices. These results are then used to forecast how farmers might change their irrigation and crop choice decisions if climate changes. The model predicts African farmers would adopt irrigation more often under a very hot and dry climate scenario but less often with a mild and wet scenario. However, farms in the deserts, lowland humid forest, or mid elevation humid forest would reduce irrigation even in the very hot and dry climate scenario. Area under fruits and vegetables would increase Africa-wide with the very hot and dry climate scenario, except in the lowland semi-arid agro-ecological zone. Millet would increase overall under the mild and wet scenario, but decline substantially in the lowland dry savannah and lowland semi-arid agro-ecological zones. Maize would be chosen less often across all the agro-ecological zones under both climate scenarios. Wheat would decrease across Africa. The authors recommend that care must be taken to match adaptations to local conditions because the optimal adaptation would depend on the agro-ecological zone and the climate scenario.
openalex: W3124307662 mag: 3124307662
Keywords: openalex:import

Will African Agriculture Survive Climate Change? - Kurukulasuriya, Pradeep; Mendelsohn, Robert; Hassan, Rashid M.; Benhin, James; Deressa, Temesgen; Diop, Mbaye; Eid, Helmy Mohamed; Fosu, K.Y.; Gbetibouo, Glwadys Aymone; Jain, Suman; Mahamadou, Ali; Mano, Reneth; et al. (The World Bank economic review (Print), 2006)
Abstract Measurement of the likely magnitude of the economic impact of climate change on African agriculture has been a challenge. Using data from a survey of more than 9,000 farmers across 11 African countries, a cross-sectional approach estimates how farm net revenues are affected by climate change compared with current mean temperature. Revenues fall with warming for dryland crops (temperature elasticity of −1.9) and livestock (−5.4), whereas revenues rise for irrigated crops (elasticity of 0.5), which are located in relatively cool parts of Africa and are buffered by irrigation from the effects of warming. At first, warming has little net aggregate effect as the gains for irrigated crops offset the losses for dryland crops and livestock. Warming, however, will likely reduce dryland farm income immedia-tely. The final effects will also depend on changes in precipitation, because revenues from all farm types increase with precipitation. Because irrigated farms are less sensitive to climate, where water is available, irrigation is a practical adaptation to climate change in Africa.
openalex: W2117807705 mag: 2117807705
Keywords: openalex:import

Will African Agriculture Survive Climate Change? - Kurukulasuriya, Pradeep; Mendelsohn, Robert; Hassan, Rashid M.; Benhin, James; Deressa, Temesgen; Diop, Mbaye; Eid, Helmy Mohamed; Fosu, K.Y.; Gbetibouo, Glwadys Aymone; Jain, Suman; Mahamadou, Ali; Mano, Reneth; et al. (The World Bank economic review (Print), 2006)
Abstract Measurement of the likely magnitude of the economic impact of climate change on African agriculture has been a challenge. Using data from a survey of more than 9,000 farmers across 11 African countries, a cross-sectional approach estimates how farm net revenues are affected by climate change compared with current mean temperature. Revenues fall with warming for dryland crops (temperature elasticity of −1.9) and livestock (−5.4), whereas revenues rise for irrigated crops (elasticity of 0.5), which are located in relatively cool parts of Africa and are buffered by irrigation from the effects of warming. At first, warming has little net aggregate effect as the gains for irrigated crops offset the losses for dryland crops and livestock. Warming, however, will likely reduce dryland farm income immedia-tely. The final effects will also depend on changes in precipitation, because revenues from all farm types increase with precipitation. Because irrigated farms are less sensitive to climate, where water is available, irrigation is a practical adaptation to climate change in Africa.
openalex: W2117807705 mag: 2117807705
Keywords: openalex:import

Will African Agriculture Survive Climate Change? - Kurukulasuriya, Pradeep; Mendelsohn, Robert; Hassan, Rashid M.; Benhin, James; Deressa, Temesgen; Diop, Mbaye; Eid, Helmy Mohamed; Fosu, K.Y.; Gbetibouo, Glwadys Aymone; Jain, Suman; Mahamadou, Ali; Mano, Reneth; et al. (The World Bank economic review (Print), 2006)
Abstract Measurement of the likely magnitude of the economic impact of climate change on African agriculture has been a challenge. Using data from a survey of more than 9,000 farmers across 11 African countries, a cross-sectional approach estimates how farm net revenues are affected by climate change compared with current mean temperature. Revenues fall with warming for dryland crops (temperature elasticity of −1.9) and livestock (−5.4), whereas revenues rise for irrigated crops (elasticity of 0.5), which are located in relatively cool parts of Africa and are buffered by irrigation from the effects of warming. At first, warming has little net aggregate effect as the gains for irrigated crops offset the losses for dryland crops and livestock. Warming, however, will likely reduce dryland farm income immedia-tely. The final effects will also depend on changes in precipitation, because revenues from all farm types increase with precipitation. Because irrigated farms are less sensitive to climate, where water is available, irrigation is a practical adaptation to climate change in Africa.
openalex: W2117807705 mag: 2117807705
Keywords: openalex:import

Will African Agriculture Survive Climate Change? - Kurukulasuriya, Pradeep; Mendelsohn, Robert; Hassan, Rashid M.; Benhin, James; Deressa, Temesgen; Diop, Mbaye; Eid, Helmy Mohamed; Fosu, K.Y.; Gbetibouo, Glwadys Aymone; Jain, Suman; Mahamadou, Ali; Mano, Reneth; et al. (The World Bank economic review (Print), 2006)
Abstract Measurement of the likely magnitude of the economic impact of climate change on African agriculture has been a challenge. Using data from a survey of more than 9,000 farmers across 11 African countries, a cross-sectional approach estimates how farm net revenues are affected by climate change compared with current mean temperature. Revenues fall with warming for dryland crops (temperature elasticity of −1.9) and livestock (−5.4), whereas revenues rise for irrigated crops (elasticity of 0.5), which are located in relatively cool parts of Africa and are buffered by irrigation from the effects of warming. At first, warming has little net aggregate effect as the gains for irrigated crops offset the losses for dryland crops and livestock. Warming, however, will likely reduce dryland farm income immedia-tely. The final effects will also depend on changes in precipitation, because revenues from all farm types increase with precipitation. Because irrigated farms are less sensitive to climate, where water is available, irrigation is a practical adaptation to climate change in Africa.
openalex: W2117807705 mag: 2117807705
Keywords: openalex:import; openalex:yes

Will African Agriculture Survive Climate Change? - Kurukulasuriya, Pradeep; Mendelsohn, Robert; Hassan, Rashid M.; Benhin, James; Deressa, Temesgen; Diop, Mbaye; Eid, Helmy Mohamed; Fosu, K.Y.; Gbetibouo, Glwadys Aymone; Jain, Suman; Mahamadou, Ali; Mano, Reneth; et al. (The World Bank economic review (Print), 2006)
Abstract Measurement of the likely magnitude of the economic impact of climate change on African agriculture has been a challenge. Using data from a survey of more than 9,000 farmers across 11 African countries, a cross-sectional approach estimates how farm net revenues are affected by climate change compared with current mean temperature. Revenues fall with warming for dryland crops (temperature elasticity of −1.9) and livestock (−5.4), whereas revenues rise for irrigated crops (elasticity of 0.5), which are located in relatively cool parts of Africa and are buffered by irrigation from the effects of warming. At first, warming has little net aggregate effect as the gains for irrigated crops offset the losses for dryland crops and livestock. Warming, however, will likely reduce dryland farm income immedia-tely. The final effects will also depend on changes in precipitation, because revenues from all farm types increase with precipitation. Because irrigated farms are less sensitive to climate, where water is available, irrigation is a practical adaptation to climate change in Africa.
openalex: W2117807705 mag: 2117807705
Keywords: openalex:import; openalex:yes

Will African Agriculture Survive Climate Change? - Kurukulasuriya, Pradeep; Mendelsohn, Robert; Hassan, Rashid M.; Benhin, James; Deressa, Temesgen; Diop, Mbaye; Eid, Helmy Mohamed; Fosu, K.Y.; Gbetibouo, Glwadys Aymone; Jain, Suman; Mahamadou, Ali; Mano, Reneth; et al. (The World Bank economic review (Print), 2006)
Abstract Measurement of the likely magnitude of the economic impact of climate change on African agriculture has been a challenge. Using data from a survey of more than 9,000 farmers across 11 African countries, a cross-sectional approach estimates how farm net revenues are affected by climate change compared with current mean temperature. Revenues fall with warming for dryland crops (temperature elasticity of −1.9) and livestock (−5.4), whereas revenues rise for irrigated crops (elasticity of 0.5), which are located in relatively cool parts of Africa and are buffered by irrigation from the effects of warming. At first, warming has little net aggregate effect as the gains for irrigated crops offset the losses for dryland crops and livestock. Warming, however, will likely reduce dryland farm income immedia-tely. The final effects will also depend on changes in precipitation, because revenues from all farm types increase with precipitation. Because irrigated farms are less sensitive to climate, where water is available, irrigation is a practical adaptation to climate change in Africa.
openalex: W2117807705 mag: 2117807705
Keywords: openalex:import